Scheimpflug lens densitometry and ocular wavefront aberrations in patients with mild nuclear cataract - Faria-Correia, Fernando (2016)
To test correlations between Scheimpflug optical densitometry and ocular higher-order aberrations (HOAs) in patients with mild nuclear cataract.